2014
DOI: 10.1007/s11427-014-4647-9
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding proteins in neurological diseases

Abstract: Emerging studies support that RNA-binding proteins (RBPs) play critical roles in human biology and pathogenesis. RBPs are essential players in RNA processing and metabolism, including pre-mRNA splicing, polyadenylation, transport, surveillance, mRNA localization, mRNA stability control, translational control and editing of various types of RNAs. Aberrant expression of and mutations in RBP genes affect various steps of RNA processing, altering target gene function. RBPs have been associated with various disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 170 publications
(118 reference statements)
0
47
0
Order By: Relevance
“…Jung et al, 2014). RBPs play critical roles during these processes by regulating RNA metabolism to modify gene expression in neurons (Zhou et al, 2014). This idea gains further support from human genetic studies that show that mutations in the genes of several RBPs are associated with neurological diseases (Liu-Yesucevitz et al, 2011;Gao and Taylor, 2014).…”
Section: Regulation Of Synaptic and Autism-related Genes By Rbfox1 Inmentioning
confidence: 93%
See 3 more Smart Citations
“…Jung et al, 2014). RBPs play critical roles during these processes by regulating RNA metabolism to modify gene expression in neurons (Zhou et al, 2014). This idea gains further support from human genetic studies that show that mutations in the genes of several RBPs are associated with neurological diseases (Liu-Yesucevitz et al, 2011;Gao and Taylor, 2014).…”
Section: Regulation Of Synaptic and Autism-related Genes By Rbfox1 Inmentioning
confidence: 93%
“…Drosophila cytoplasmic RBFOX1 represses translation of one of its target mRNAs, the translational regulator pumilio, to regulate germ cell differentiation (Carreira-Rosario et al, 2016), indicating that RBFOX1 may either enhance or repress gene expression in the cytoplasm of cells. Recent studies showed that RBFOX2 and RBFOX3 can regulate the biogenesis of microRNAs, and RBFOX2 can bind nascent RNAs to regulate polycomb complex 2 targeting Wei et al, 2016). These data suggest that RBPs might have diverse functions in neurons and an increased understanding of RNA regulation will lead to novel therapies for a range of brain disorders.…”
Section: Regulation Of Synaptic and Autism-related Genes By Rbfox1 Inmentioning
confidence: 97%
See 2 more Smart Citations
“…Also focussed on neurodegenerative diseases such as motor neuron disease, Professor Wu Jane (IBP) and Dr Marie Mangelsdorf (QBI) provide insights into the role played by aberrant expression and mutation of genes coding for RNA-binding proteins in initiating human brain disease [9].…”
mentioning
confidence: 99%